The Impact Of Islamic Corporate Governance And Tabarru’ Fund On The Level Of Sharia Insurance Health - Yafiul Firdaus; Falikhatun Falikhatun (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
The purpose of this study to determine the impact of the number of the board of directors, the number of audit committees, the number of sharia supervisory board, and the Tabarru' Fund on the financial health level of Islamic insurance companies. This research was conducted on Sharia General Insurance companies and Sharia Life Insurance companies in Southeast Asia during the 2015-2019 period. The results of this research stated that the number of Sharia Supervisory Boards has a negative impact on the level of financial health, the number of the Board of Directors has a positive impact on the level of financial health, while the number of audit committees and the amount of Tabarru Funds has no impact on the level of financial health. This research is expected to be a reference for the development of science, especially in the field of accounting about the influence of Islamic Corporate Governance and the amount of tabarru' funds on the level of financial health of Islamic insurance companies using agency theory and sharia enterprise theory and can be used as a reference for regulators to update regulations related to Islamic Corporate Governance and tabarru funds.